Homogeneous water oxidation using peroxidase mimic [Fe-III(biuret-amide)] and analyte detection via signal amplification - Panda, C.; Dhar, B. B.; Ghosh, Munmun; Malvi, Bharmana; Bhattacharjee, Yudhajit; Sengupta, S. (Journal of Biological Inorganic Chemistry, 2014)

Selective C-H bond oxidation catalyzed by the Fe-bTAML complex: mechanistic implications - Ghosh, M. (Inorganic Chemistry, 2017)
Nonheme iron complexes bearing tetradentate N-atom-donor ligands with cis labile sites show great promise for chemoselective aliphatic C-H hydroxylation. However, several challenges still limit their widespread application. We report a mechanism-guided development of a peroxidase mimicking iron complex based on the bTAML macrocyclic ligand framework (Fe-bTAML: biuret-modified tetraamido macrocyclic ligand) as a catalyst to perform selective oxidation of unactivated 3° bonds with unprecedented regioselectivity (3°:2° of 110:1 for adamantane oxidation), high stereoretention (99%), and turnover numbers (TONs) up to 300 using mCPBA as the oxidant. Ligand decomposition pathways involving acid-induced demetalation were identified, and this led to the development of more robust and efficient Fe-bTAML complexes that catalyzed chemoselective C-H oxidation. Mechanistic studies, which include correlation of the product formed with the FeV(O) reactive intermediates generated during the reaction, indicate that the major pathway involves the cleavage of C-H bonds by FeV(O). When these oxidations were performed in the presence of air, the yield of the oxidized product doubled, but the stereoretention remained unchanged. On the basis of 18O labeling and other mechanistic studies, we propose a mechanism that involves the dual activation of mCPBA and O2 by Fe-bTAML, leading to formation of the FeV(O) intermediate. This high-valent iron oxo remains the active intermediate for most of the reaction, resulting in high regio- and stereoselectivity during product formation.